2018
DOI: 10.1039/c8cp03205j
|View full text |Cite
|
Sign up to set email alerts
|

Formation of highly ordered liquid crystalline coatings – an in situ GISAXS study

Abstract: Functional coatings based on self-assembled lyotropic liquid crystals have the potential for applications such as biosensing, drug delivery and nanotemplating. Here we demonstrate the design and in-depth characterization of glycerol monooleate based liquid crystalline coatings on silicon wafers using drop casting and spin coating techniques. In situ time-resolved grazing incidence small angle X-ray scattering (GISAXS) measurements were used to monitor the coating formation and its response to increasing relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Self-assembled structures, including micelles, microemulsions, and inverse lyotropic nonlamellar liquid crystalline phases, have attracted increasing attention for their potential applications in drug delivery. Formed by the self-assembly of biologically relevant amphiphilic lipids in excess water, these structures are in thermodynamic equilibrium with their surroundings and provide large lipid–water interfacial area for the solubilization of various bioactive molecules such as proteins and peptides or host them in their aqueous or oil domains. Encapsulation of guest molecules into the nanoparticle dispersions of such nanostructures may offer many advantages, including protection from proteolysis and oxidation. , Additionally, such self-assembled nano-objects can be designed to be responsive to various stimuli, including temperature, , light, , presence of enzymes, , and pH. These stimuli trigger structural changes in these colloidal nanoparticles and selectively modulate their activity or facilitate release of their active cargo. In this context, pH-sensitive lipid-based nanocarriers for AMPs are attractive for a wide range of pharmaceutical applications as they could provide self-regulated passive targeting to areas of specific pH in the body .…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembled structures, including micelles, microemulsions, and inverse lyotropic nonlamellar liquid crystalline phases, have attracted increasing attention for their potential applications in drug delivery. Formed by the self-assembly of biologically relevant amphiphilic lipids in excess water, these structures are in thermodynamic equilibrium with their surroundings and provide large lipid–water interfacial area for the solubilization of various bioactive molecules such as proteins and peptides or host them in their aqueous or oil domains. Encapsulation of guest molecules into the nanoparticle dispersions of such nanostructures may offer many advantages, including protection from proteolysis and oxidation. , Additionally, such self-assembled nano-objects can be designed to be responsive to various stimuli, including temperature, , light, , presence of enzymes, , and pH. These stimuli trigger structural changes in these colloidal nanoparticles and selectively modulate their activity or facilitate release of their active cargo. In this context, pH-sensitive lipid-based nanocarriers for AMPs are attractive for a wide range of pharmaceutical applications as they could provide self-regulated passive targeting to areas of specific pH in the body .…”
Section: Introductionmentioning
confidence: 99%
“…[39a] Recently, our team demonstrated the design and application of lamellar and non-lamellar liquid crystalline coatings for the antimicrobial functionalization of surfaces. [40] A facile method was established to fabricate stable GMO-based coatings on surfaces by depositing GMO/ethanol mixtures using methods such as spin-coating or drop-casting; followed by solvent evaporation. [40] Synchrotron grazing-incidence small-angle X-ray scattering (GISAXS) and atomic force microscopy (AFM) showed that the resulting GMO-based coatings self-assemble into lamellar structures at low hydration with transformations to a fluid isotropic (sponge) phase followed by a second lamellar and the bicontinu-Fig.…”
Section: Antimicrobial Surface Functionalization With Lipidbased Coat...mentioning
confidence: 99%
“…For instance, a homogeneous film of GMO-based inverse-type nonlamellar liquid crystals on unmodified silicon wafers could be formed when GMO was solubilized in ethanol but not in chloroform. 19 Annealing effects during solvent evaporation and structural modifications due to residual, strongly bound ethanol molecules at the substrate−liquid crystal interface was held responsible for this effect. 19 The study of surface nanostructures under hydrated conditions requires advanced experimental techniques such as synchrotron grazing-incidence small-angle X-ray scattering (GISAXS) with specifically designed sample environments for excess-water measurements.…”
Section: Introductionmentioning
confidence: 99%
“…19 Annealing effects during solvent evaporation and structural modifications due to residual, strongly bound ethanol molecules at the substrate−liquid crystal interface was held responsible for this effect. 19 The study of surface nanostructures under hydrated conditions requires advanced experimental techniques such as synchrotron grazing-incidence small-angle X-ray scattering (GISAXS) with specifically designed sample environments for excess-water measurements. The application of GISAXS also allows the study of buried coating structures in a nondestructive way, providing insights into the contribution of the substrate surface to the self-assembly processes.…”
Section: Introductionmentioning
confidence: 99%